Routine follow up of breast cancer in primary care: randomised trial. - Grunfeld, E; Mant, D; Yudkin, P; Adewuyi-Dalton, R; Cole, D; Stewart, J; Fitzpatrick, R; Vessey, M (1996)
OBJECTIVE: To assess the effect on time to diagnosis of recurrence and on quality of life of transferring primary responsibility for follow up of women with breast cancer in remission from hospital to general practice. DESIGN: Randomised controlled trial with 18 month follow up in which women received routine follow up either in hospital or in general practice. SUBJECTS AND SETTING: 296 women with breast cancer in remission receiving regular follow up care at district general hospitals in England. MAIN OUTCOME MEASURES: Time between first presentation of symptoms to confirmation of recurrence; quality of life measured by specific dimensions of the SF-36 schedule, the EORTC symptom scale, and hospital anxiety and depression scale. RESULTS: Most recurrences (18/26, 69%) presented as interval events, and almost half (7/16, 44%) of the recurrences in the hospital group presented first to general practice. The median time to hospital confirmation of recurrence was 21 days in the hospital group (range 1-376 days) and 22 days in the general practice group (range 4-64). The differences between groups in the change in SF-36 mean scores from baseline were small: -1.8 (95% confidence interval -7.2 to 3.5) for social functioning, 0.5 (-4.1 to 5.1) for mental health, and 0.6 (-3.6 to 4.8) for general health perception. The change from baseline in the mean depression score was higher in the general practice group at the mid-trial assessment (difference 0.6, 0.1 to 1.2) but there was no significant difference between groups in the anxiety score or the EORTC scales. CONCLUSION: General practice follow up of women with breast cancer in remission is not associated with increase in time to diagnosis, increase in anxiety, or deterioration in health related quality of life. Most recurrences are detected by women as interval events and present to the general practitioner, irrespective of continuing hospital follow up.